KEANEKARAGAMAN JENIS SERANGGA DETRITIVOR DI DESA PAMPANG HARAPAN TAMAN NASIONAL GUNUNG PALUNG (Diversity of Detritivor Insect Species in Pampang Harapan Village, Gunung Palung National Park) - Herlina Darwati; catur aditia kamalramadan; Slamet Rifanjani (JURNAL HUTAN LESTARI, 2023)
The diversity of insect detritivores can be done by several methods, including pitfall traps and barlese funnels. This study aims to obtain and compare data on the variety and abundance of ground surface insects as detritivores in two different forest types. The research was conducted in Pampang Harapan Village, Gunung Palung National Park Area, for ± two months. To get data on the diversity of insect detritivores found, insects will group them based on their role. The data obtained is analyzed and receives a value of 1.6, which is moderate diversity for both forest types. Then, compare the abundance data using species similarity analysis and get a value of 69.565%, which shows the importance of species similarity in both forest types has high species similarity. Then use the T-test to get the difference in the two forest types and get a T count value of 1.644, which is smaller than the t table of degrees of freedom 9; confidence 0.025% is worth 2.262 (t-count < t-table), proves that there is no significant difference between detritivores in lowland forests and detritivores in coastal forests Keywords: Abundance, Detritivor, Species similarityAbstrakKeanekaragaman jenis serangga detritivor dapat dilakukan dengan beberapa metode di antaranya pitfall trap dan corong barlese. Penelitian bertujuan mendapatkan dan membandingkan data keanekaragaman dan kelimpahan jenis serangga permukaan tanah sebagai detritivor pada dua tipe hutan dataran rendah dan hutan pantai. Penelitian dilaksanakan di Desa Pampang Harapan Kawasan Taman Nasional Gunung Palung selama ±2 bulan. data keanekaragaman jenis serangga detritivor serangga yang ditemukan dikelompokkan berdasarkan perannya dengan nilai 1,6 yaitu keanekaragaman sedang untuk kedua tipe hutan. Nilai kesamaan jenis 96.565% yang menunjukkan nilai kesamaan jenis di kedua tipe hutan memiliki kesamaan jenis yang tinggi. T hitung 1,644 yang lebih kecil dari t tabel derajat bebas 9, kepercayaan 0,025% bernilai 2,262 (t-hitung < t-tabel) membuktikan bahwa tidak ada perbedaan yang signifikan antara serangga detritivor di hutan dataran rendah dan serangga detritivor di hutan pantaiKata kunci : Detritivor, Gunung Palung, Kelimpahan, Kesamaan